High-density grafting of carbon nanotube/carbon nanofiber hybrid on carbon fiber surface by vacuum filtration for effective interfacial reinforcement of its epoxy composites. (7th July 2022) - Wu, Qing; Bai, Huanhuan; Gao, Aijun; Zhu, Jianfeng
Abstract: Attempts to incorporate nanofillers onto the circumferential surface of traditional high-performance fibers via vacuum filtration toward gaining improved interfacial adhesion of corresponding composites are still in its infancy. Herein, we first achieve high-density grafting of carbon nanotube/carbon nanofiber (CNT/CNF) successfully on carbon fiber surface. The treated fibers with depositing positive and negative 5 ml CNT/CNF nanohybrid suspension shows 40.7% (85.4 MPa) gain in interfacial shear strength over that of untreated fiber (60.7 MPa). The reinforcement effect is mainly ascribed to the markedly improved wettability, which provides sufficient hydrogen bonding and pinning effect at interphase zone. Moreover, appropriate amount of CNT/CNF hybrid endows the interphase with gradual modulus transition, minimizing the stress concentration. Our research offers a promising, efficient and green approach for fully utilization of diverse nanofillers and rich interfacial interactions to realize substantial enhancement in interfacial adhesion in the future. Graphical abstract: Image 1